The emerging role of Rab GTPases in the pathogenesis of Parkinson's disease. Issue 2 (9th January 2018) - Gao, Yujing; Wilson, Gabrielle R.; Stephenson, Sarah E. M.; Bozaoglu, Kiymet; Farrer, Matthew J.; Lockhart, Paul J.
ABSTRACT: The identification of pathogenic mutations in Ras analog in brain 39B ( RAB39B ) and Ras analog in brain 32 ( RAB32 ) that cause Parkinson's disease (PD) has highlighted the emerging role of protein trafficking in disease pathogenesis. Ras analog in brain (Rab) Guanosine triphosphatase (GTPase) function as master regulators of membrane trafficking, including vesicle formation, movement along cytoskeletal networks, and membrane fusion. Recent studies have linked Rab GTPases with α‐synuclein, Leucine‐rich repeat kinase 2, and Vacuolar protein sorting 35, 3 key proteins in PD pathogenesis. In this review, we discuss the various RAB GTPases associated with PD, current progress in the research, and potential future directions. Investigations into the function of RAB GTPases will likely provide significant insight into the etiology of PD and identify novel therapeutic targets for a currently incurable disease. © 2018 International Parkinson and Movement Disorder Society